THU0031 Phenotype of foxp3+ regulatory t-cells expanded by the il-2 mutein, amg 592 in healthy subjects in phase 1, first-in-human study. (12th June 2018) - Gorski, K.S.; Stern, J.; Hsu, Y.-H.; Anderson, A.; Boedigheimer, M.; Tchao, N.
Abstract : Background: Low-dose interleukin-2 (IL-2) therapy expands regulatory T cells (Treg) and provides clinical benefit for inflammatory diseases. AMG 592 is an investigational IL-2 mutein designed to expand Treg more selectively than recombinant IL-2 (aldesleukin). In a phase 1, double-blind, placebo (PBO)-controlled first-in-human (FIH) study, we investigated the safety and tolerability of AMG 592 and pharmacodynamic (PD) effects on Treg. Objectives: We recently presented FIH study results including summary of safety, PK and PD. 1 Here we extend those findings by exploring phenotypes of AMG 592 expanded Foxp3 + Treg subsets using flow cytometry. We compared both analysis using predefined gates and unsupervised gating. Potential implications for dose selection and mechanism of action will be discussed. Methods: In the FIH study, healthy subjects in multiple ascending dose cohorts received a single subcutaneous dose of AMG 592 (n=6 per cohort) or placebo (n=2 per cohort). Pharmacodynamic response was evaluated for 28 days after treatment. In addition to enumerating CD4 + Foxp3 + Treg we evaluated changes in Treg subsets after AMG 592 treatment. Changes from baseline were analysed with linear mixed effects models with visit, dose level, and baseline result as main effects. To identify cell subsets, independent of predefined gates the same data were also evaluated with unsupervised gating tools using raw data from days 1, 8, 15 and 22. Results: We observed a robust, dose-dependent expansion of Tregs that peaked at day 8 (~4–5 fold increase) and remained elevated above baseline up to day 29 for the highest doses. Expanded Tregs had increased levels of CD25 and Foxp3, and were enriched for CD31 + recent thymic emigrants (RTE). Both naïve and memory Treg increases peaked at day 8, however, naïve Treg including RTE persisted at elevated levels through day 29 while memory Treg returned to normal levels earlier. The majority of Treg expressed the transcription factor Helios. Furthermore, expanded Tregs expressed higher proportions of PD-1. Unsupervised gating analysis identified several primary clusters of expanded Treg, one including naïve and RTE Treg and another including memory Treg with elevated levels of HLA-DR expression. Evaluation of these clusters over time suggests that both increase initially at day 8 followed by preferential persistence of cells in the naïve over memory Treg cluster by day 22. Conclusions: Foxp3 + Treg were expanded in a dose dependent fashion in healthy subjects treated with AMG 592. The phenotype of expanded Treg included elevation of CD25 and Foxp3 as well as enrichment for PD-1 positive subsets. Taken together the increase in Treg with an RTE phenotype and persistence of naïve Treg suggests that AMG 592 may increase diversity of the Treg pool as a possible mechanism of action in addition to effects on memory Treg. Reference: [1] ASH 2017, AMG 592 Is an Investigational IL-2 Mutein That Induces Highly Selective Expansion of Regulatory T Cells, Nadia Tchao, Kevin S Gorski, Theresa Yuraszeck, Sue J Sohn, Katsuhiko Ishida, Hansen Wong and Kyong Park Disclosure of Interest: K. Gorski Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., J. Stern Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., Y.-H. Hsu Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., A. Anderson Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., M. Boedigheimer Shareholder of: Amgen, Inc., Employee of: Amgen, Inc., N. Tchao Shareholder of: Amgen, Inc., Employee of: Amgen, Inc.